2022
DOI: 10.15282/jmes.16.1.2022.07.0690
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of combustion parameters for CRDI small single cylinder diesel engine by using response surface method

Abstract: Limited fossil fuel’s reservoir capacity and pollution caused by them are the big problem today in the world. The small diesel engine, working with a conventional fuel injection system was the major contributor to this. The current study represented a statistical investigation of such a small diesel engine. A mechanical fuel injection system of the small diesel engine was retofitted with a simple version of the electronic common rail diesel injection (CRDI) system in the present study. The effect of combustion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This array of benefits has prompted numerous researchers to conduct experiments on small-scale diesel engines. They often perform statistical analyses by retrofitting the common rail direct injection (CRDI) system and making requisite adjustments to its associated characteristics [4][5][6][7][8][9][10][11][12]. In a test on a diesel engine with CRDI assistance, Hwang et al [6] found that the combustion parameters were significantly improved over those of the conventional system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This array of benefits has prompted numerous researchers to conduct experiments on small-scale diesel engines. They often perform statistical analyses by retrofitting the common rail direct injection (CRDI) system and making requisite adjustments to its associated characteristics [4][5][6][7][8][9][10][11][12]. In a test on a diesel engine with CRDI assistance, Hwang et al [6] found that the combustion parameters were significantly improved over those of the conventional system.…”
Section: Introductionmentioning
confidence: 99%
“…In a test on a diesel engine with CRDI assistance, Hwang et al [6] found that the combustion parameters were significantly improved over those of the conventional system. Dond and Gulhane [7][8][9][10] conducted experiments on a CRDI singlecylinder diesel engine and determined the optimum values for injection system parameters, such as pilot and main injection timing of fuel, along with the quantity of fuel to be supplied during these two periods. The same injection parameters were considered in the present study as well.…”
Section: Introductionmentioning
confidence: 99%